The Beginning and the Development of the Fellows of Eucharist Movement (1969–1973) - Labanauskas, Ramūnas (Genocidas ir rezistencija, 2003)
The most significant factors that had determined formation of the Catholic resistance and the Fellows of Eucharist Movement (the EBS), as the integral part of the previous, were thought to be the 2nd Congress of Vatican and suspension of Nikita Chruschov in 1964. The Congress encouraged all links of the Church to be more active among the laity, yet polarized the clergy a lot: the hierarchy met the decisions of the Congress with hostility and purposely impeded implementation of reforms, while a number of young priests who enthusiastically agreed with the new teaching of the Church joined the opposition. The ones to distinguish themselves were Rev. Alfonsas Svarinskas, Juozas Zdebskis, Sigitas Tamkevičius, Petras Našlėnas. Participating in meetings of the believers since 1966, often organized by publishers and distributors of the religious literature, they were preparing ground for actions of the Fel- lows of Eucharist Movement. They were actively assisted by sister monkhoods, especially the Sisters’ Congregation of the Eucharist Jesus. Features peculiar to the latter also made a large effect on the character of the EBS and its organizational structure.